Bioleaching performance of vanadium-bearing smelting ash by Acidithiobacillus ferrooxidans for vanadium recovery. (15th June 2023) - Guo, Xiaoxiao; Chen, Siming; Han, Yawei; Hao, Chunbo; Feng, Xiujuan; Zhang, Baogang
Abstract: The bioleaching process is widely used in the treatment of ores or solid wastes, but little is known about its application in the treatment of vanadium-bearing smelting ash. This study investigated bioleaching of smelting ash with Acidithiobacillus ferrooxidans . The vanadium-bearing smelting ash was first treated with 0.1 M acetate buffer and then leached in the culture of Acidithiobacillus ferrooxidans . Comparison between one-step and two-step leaching process indicated that microbial metabolites could contribute to the bioleaching. The Acidithiobacillus ferrooxidans demonstrated a high vanadium leaching potential, solubilizing 41.9% of vanadium from the smelting ash. The optimal leaching condition was determined, which was 1% pulp density, 10% inoculum volume, an initial pH of 1.8, and 3 Fe 2+ g/L. The compositional analysis showed that the fraction of reducible, oxidizable, and acid-soluble was transferred into the leaching liquor. Therefore, as the alternative to the chemical/physical process, an efficient bioleaching process was proposed to enhance the recovery of vanadium from the vanadium-bearing smelting ash. Graphical abstract: Image 1 Highlights: The Acidithiobacillus ferrooxidans accomplished high vanadium leaching efficiency. Up to 41.9% of vanadium was leached out from the vanadium-bearing smelting ash. The microbial metabolites leached 14.2% vanadium from the smelting ash. The fraction of reducible, oxidizable, and acid-soluble was reduced to ≤30%. Optimal pulp density, inoculum volume, pH and concentration of Fe 2+ was determined.